Critical thinking, developmental learning and adaptive flexibility in organizational leaders. - Robert Duchesne (Adult Education Research Conference, 1997)
Organizational leaders in today's global marketplace must continually make decisions, solve problems, and chart effective courses of action to ensure that their companies survive and flourish. The ability to think critically is essential for today's leaders, yet leaders are often unable to do so. This study examined how developmental learning and adaptive flexibility related to the level of critical thinking in a sample of organizational leaders. Results showed years of education to be the only significant predictor of critical thinking in the leaders studied. Adaptive flexibility scores indicate minimal levels of reflective observation suggesting automatization of decision-making. The factor analysis of developmental learning experiences identified several factors that characterize the developmental learning of the leaders studied. The theoretical and practical significance of the findings is discussed.